2014
DOI: 10.1007/s13197-014-1546-9
|View full text |Cite
|
Sign up to set email alerts
|

Drying of chilli in a combined infrared and hot air rotary dryer

Abstract: The investigation of an economical and efficient drying method for chilli is beneficial because it could provide a means of overcoming the drawbacks of traditional drying methods: high operating power and long drying time, which result in a decrease in the quality of the chilli. This study involved the design and development of a combined infrared and hot air laboratory-scale rotary dryer, which consists of three operating modes: hot air, infrared, and combined infrared and hot air. Drying experiments were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…They also reported that MIR-HAD gave a better-uniformed product than HAD, with minimal shrinkage and lower hardness upon rehydration. Similar findings have been reported by Mihindukulasuriya and Jayasuriya (2015). They observed a 60% reduction in drying time when compared with HAD alone during the IR-HAD of ripe chilli.…”
Section: Fruits and Vegetables El-mesery And Mwithigasupporting
confidence: 89%
“…They also reported that MIR-HAD gave a better-uniformed product than HAD, with minimal shrinkage and lower hardness upon rehydration. Similar findings have been reported by Mihindukulasuriya and Jayasuriya (2015). They observed a 60% reduction in drying time when compared with HAD alone during the IR-HAD of ripe chilli.…”
Section: Fruits and Vegetables El-mesery And Mwithigasupporting
confidence: 89%
“…Drying is not only the traditionally adopted method in preserving food and perishable vegetables but it also reduces the storage volume as well as increasing shelf life . Different drying methods are adopted to optimize the compromise between efficiency and quality, such as sun drying (SD), hot air drying (HD), microwave drying and freeze drying (FD) . SD is the traditionally adopted method for pepper drying, which takes 7–20 days (depending on the weather) to reduce the moisture content to the desired level of 10–15% .…”
Section: Introductionmentioning
confidence: 99%
“…Pengeringan bukan hanya metode yang diadopsi secara tradisional dalam melestarikan makanan dan sayuran yang mudah rusak tetapi juga mengurangi volume penyimpanan serta meningkatkan umur simpan (Reis et al, 2013). Metode pengeringan yang berbeda diadopsi untuk mengoptimalkan kompromi antara efisiensi dan kualitas, seperti pengeringan matahari, pengeringan udara panas (Fudholi et al, 2013;Mihindukulasuriya et al, 2015), pengeringan microwave (Saengrayap et al, 2015) dan pengeringan beku (Topuz et al, 2011). Pengeringan matahari adalah metode yang diadopsi secara tradisional untuk pengeringan cabai dengan durasi waktu 7-20 hari (tergantung pada cuaca) yang bertujuan mengurangi kadar air hingga tingkat yang diinginkan 10-15% (Janjai et al, 2011).…”
Section: Pendahuluanunclassified